Pengaruh Pembelajaran Praktik pada Mata Pelajaran Produk Kreatif dan Kewirausahaan Terhadap Minat Berwirausaha Siswa Kelas XII Perhotelan di SMK Negeri 3 Solok - Putri, Melliyati; Putri, Desi Armi Eka; Ikhwan, Ikhwan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the influence of practical learning on creative product subjects and entrepreneurial interest in class XII hospitality students at SMK Negeri 3 Solok.This type of research is quantitative research. The population in the study was all class XII students at SMK Negeri 3 Solok who were registered in the 2024/2025 academic year, namely 64 people with total sampling technique. Data was collected through observation and distributed questionnaires. The analysis technique used is a simple linear regression analysis technique. The results of the research show that: practical learning with a significance level of 0.05, the magnitude of the influence of practical learning on interest in entrepreneurship is 27.1% and the tcount value is 4.804 while the ttable is 1.998, so the hypothesis is accepted. Based on the conclusion in this research, there is a positive and significant influence between practical learning on students' interest in entrepreneurship. Suggestions for students at SMK Negeri 3 Solok to be more active and enthusiastic during practical learning because it can improve skills and knowledge